Quinti Septimi Florentis Tertulliani De anima - Tertullian, approximately 160-approximately 230. (Vigiliae Christianae, Supplements, 2010)
The 'Supplements to Vigiliae Christianae' series was launched in 1987 with the publication of Tertullianus, De Idololatria , a critical text with translation and commentary by J.H. Waszink and J.C.M. van Winden (partly based on a manuscript left behind by P.G. van der Nat). It seems appropriate, therefore, that the 100th volume to appear in the 'Supplements to Vigiliae Christianae' series should be an updated reprint of J.H. Waszink's monumental and authoritative edition of Tertullian's De Anima . This volume contains the complete contents of the first edition, to which we have added a brief overview of J.H. Waszink's scholarly career, an English translation of the greater part of the introduction to his German translation of De Anima of 1980 and a list of corrections authorized by him.